1996
DOI: 10.1016/s0009-9236(96)90114-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tacrine oral clearance by cimetidine

Abstract: Plasma tacrine, 1-hydroxytacrine, 2-hydroxytacrine, and 4-hydroxytacrine concentrations were measured in 12 healthy elderly subjects in this nonblinded two-period study to assess the effect of multiple doses of cimetidine on single-dose tacrine pharmacokinetics. Subjects received 40 mg tacrine (Cognex) alone and during multiple-dose cimetidine (300 mg four times a day) administration. Overall, tacrine and cimetidine were well tolerated by healthy elderly subjects. After coadministration of cimetidine with tacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…CYP1A2. The importance of CYP1A2 in the elimination of both tacrine and 1‐OH tacrine would also account for why treatment with cimetidine has been shown to cause increases in the AUC of 1‐OH tacrine in addition to increases in the AUC of parent tacrine [40]. It seems reasonable to assume that competition between tacrine and its metabolites for CYP1A2 metabolism may complicate the relationship between tacrine clearance and CYP1A2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…CYP1A2. The importance of CYP1A2 in the elimination of both tacrine and 1‐OH tacrine would also account for why treatment with cimetidine has been shown to cause increases in the AUC of 1‐OH tacrine in addition to increases in the AUC of parent tacrine [40]. It seems reasonable to assume that competition between tacrine and its metabolites for CYP1A2 metabolism may complicate the relationship between tacrine clearance and CYP1A2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…45 The oral clearance of tacrine was inhibited by 30% after administration with cimetidine. 46 In the present work we studied chitosan nanoparticles as a new delivery system for the anti-Alzheimer drug tacrine and the effect of Polysorbate 80 coating on its biodistribution studies on rats.…”
mentioning
confidence: 99%
“…Studies on the effect of cimetidine after a single dose showed a clear relationship between blood concentration and extent of inhibition of basal gastric acid 7 . When cimetidine was co-administered with other drugs clinically significant drug-drug interactions were observed and reported 8,9 . The excretion rate of cimetidine may invariably determine the duration of action.…”
Section: Introductionmentioning
confidence: 99%